2016
DOI: 10.1021/acsami.6b00548
|View full text |Cite
|
Sign up to set email alerts
|

Human Interactive Triboelectric Nanogenerator as a Self-Powered Smart Seat

Abstract: A lightweight, flexible, cost-effective, and robust, single-electrode-based Smart Seat-Triboelectric Nanogenerator (SS-TENG) is introduced as a promising eco-friendly approach for harvesting energy from the living environment, for use in integrated self-powered systems. An effective method for harvesting biomechanical energy from human motion such as walking, running, and sitting, utilizing widely adaptable everyday contact materials (newspaper, denim, polyethylene covers, and bus cards) is demonstrated. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…The theory of the triboelectric nanogenerator was firstly proposed by Wang [2]. Based on the theory, researchers have developed numbers of triboelectric nanogenerator [3][4][5], which had been widely used in many fields, such as the energy collection [6][7][8][9], industrial sensors [10][11][12][13], medical equipment [14,15], leisure equipment [16][17][18][19], geological monitoring [20,21], and other industrial applications [22,23]. Therefore, the triboelectric nanogenerator brings hope for solving the problems of vibration energy collection and vibration measurement in downhole.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of the triboelectric nanogenerator was firstly proposed by Wang [2]. Based on the theory, researchers have developed numbers of triboelectric nanogenerator [3][4][5], which had been widely used in many fields, such as the energy collection [6][7][8][9], industrial sensors [10][11][12][13], medical equipment [14,15], leisure equipment [16][17][18][19], geological monitoring [20,21], and other industrial applications [22,23]. Therefore, the triboelectric nanogenerator brings hope for solving the problems of vibration energy collection and vibration measurement in downhole.…”
Section: Introductionmentioning
confidence: 99%
“…The operation of TENGs is depended on triboelectrification (or contact electrification) and electrostatic induction [11], and the fundamental theory is according to Maxwell's displacement current and change in surface polarization [12]. Since the first invention of TENG in 2012, it has been extensively investigated and well confirmed that the potential of wide application is ranging from powering small electronic devices for self-powered systems, functioning as active sensors for medical, infrastructural, human-machine, environmental monitoring, and security [13][14][15][16][17][18][19][20]. Various types of wasted mechanical energies in our daily life, such as human motion, vibration, wind, and flowing water can be utilized by different TENG structures.…”
Section: Introductionmentioning
confidence: 99%
“…Offering good conversion efficiency, the TENG is capable of harvesting small vibration energy, motion energy, wind energy, and wave and tidal energy. Chandrasekhar et al designed self‐powered smart seat harvesting biomechanical energy from human motion. The smart seat TENG yielded a V oc of 52 V and an I sc of 5.2 μA.…”
Section: Introductionmentioning
confidence: 99%